2002
DOI: 10.1080/02652030110091163
|View full text |Cite
|
Sign up to set email alerts
|

Fate of patulin in the presence of the yeastSaccharomyces cerevisiae

Abstract: Patulin is known to become analytically non-detectable during the production of cider from contaminated apple juice. The fate of [14C]-labelled patulin during the alcoholic fermentation of apple juice was studied. Three commercial cider strains of Saccharomyces cerevisiae degraded patulin during active fermentative growth, but not when growing aerobically. The products of patulin degradation were more polar than patulin itself and remained in the clarified fermented cider. Patulin did not appear to bind to yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
97
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(104 citation statements)
references
References 21 publications
6
97
0
1
Order By: Relevance
“…The products of biodegradation of individual mycotoxins differ, depending on the chemical bonds within each mycotoxin that are targeted by the respective biodegradation pathway. For the most part, the products of patulin biodegradation had not been identified (Anderson et al 1979;Harwig et al 1973;Stinson et al 1978;Sumbu et al 1983) until recently, when ascladiol (Moss and Long 2002;Ricelli et al 2007) and desoxypatulinic acid (DPA) were characterized. The two compounds probably use alternative pathways, since one process is anaerobic (leading to ascladiol) and the other is aerobic (leading to DPA).…”
Section: Resultsmentioning
confidence: 99%
“…The products of biodegradation of individual mycotoxins differ, depending on the chemical bonds within each mycotoxin that are targeted by the respective biodegradation pathway. For the most part, the products of patulin biodegradation had not been identified (Anderson et al 1979;Harwig et al 1973;Stinson et al 1978;Sumbu et al 1983) until recently, when ascladiol (Moss and Long 2002;Ricelli et al 2007) and desoxypatulinic acid (DPA) were characterized. The two compounds probably use alternative pathways, since one process is anaerobic (leading to ascladiol) and the other is aerobic (leading to DPA).…”
Section: Resultsmentioning
confidence: 99%
“…This explains why patulin contamination in fermented drinks such as cider is usually lower than in juices and other nonfermented pome fruit-based products. 12,22,23 E-Ascladiol has no hemiacetal group (which would probably account for its slightly lower toxicity as compared to patulin), but retains the integrity of the lactone ring in its molecular structure. It is in itself considered to be a mycotoxin, although with less acute toxicity than patulin.…”
Section: Journal Of Agricultural and Food Chemistrymentioning
confidence: 99%
“…22,23 In recent years, the degradation products have been identified in the case of the biodegradation carried out by the fermentative yeast Saccharomyces cerevisiae in anaerobic conditions. 12 The final products are two different isomers of ascladiol, E-ascladiol and Z-ascladiol. E-Ascladiol is the predominant degradation compound.…”
Section: ' Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier work demonstrated that more than 99% of patulin (50 mg/L) removed during alcoholic fermentation of apple juice, while only 10% decrease was observed in the control sample (Stinson et al, 1978). Later, three commercial cider strains of S. cerevisiae degraded patulin during active fermentative growth (Moss and Long, 2002).…”
Section: Biological Methodsmentioning
confidence: 99%